THE PROSE OF THE CONQUEST: WRITING PROCEDURES IN THE CHRONICLES OF THE NEW SPAIN AND PERU, XVI CENTURY (Tzintzun, Revista de Estudios Históricos, 2022)
This article offers a rereading of the story of the conquest that the conquerors-chronicles of Peru and New Spain elaborated in the sixteenth century: Francisco de Xerez and Pedro Pizarro in the first case; Hernan Cortes and Bernal Diaz del Castillo in the second. The author finds in them a particularized, unstable prose of the conquest, which responds less to an absolute narrative freedom than to the hegemonic character of the of the political ideas established by the Spanish Empire for the colonial occupation. Registered in the studies of the historiographic turn, the article explores the narrativity constructed in the colonial chronicles. Itis not its objective to reconstruct the facts of the conquest nor to attribute veracity or falsity to the chroniclers’ sayings, but to explore in them ways of representing the past, which undoubtedly depend on the rhetoric of power sustained by the Empire.
Keywords: Colonisation espagnole; chroniques des Indes; Discours hégémonique; historiographie pré-moderne; tournant historiographique